2008
DOI: 10.1086/590460
|View full text |Cite
|
Sign up to set email alerts
|

Rural Nonfarm Employment and Incomes in the Himalayas

Abstract: Nonfarm activities generate, on average, about 60% of rural households' incomes in the Himalayas. This article analyzes the determinants of participation in nonfarm activities and of nonfarm incomes across rural households. A unique data set collected in the Himalayan region of India allows us to deal with the heterogeneity of rural nonfarm activities by using aggregations into categories that are useful both analytically and for policy purposes. We conduct an empirical inquiry that reveals that education play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…According to Micevska and Rahut (2008) recent research indicated that the rural poor engaged in nonfarm activities, both as a complement to their farm activities and as a substitute for their farm incomes. In some cases, nonfarm employment may be a coping strategy to deal with lack of access to sufficient land or with income shocks in agriculture.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Micevska and Rahut (2008) recent research indicated that the rural poor engaged in nonfarm activities, both as a complement to their farm activities and as a substitute for their farm incomes. In some cases, nonfarm employment may be a coping strategy to deal with lack of access to sufficient land or with income shocks in agriculture.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The latter has a great implication for farm families in rural Africa where population control is a matter of semantics and where children are used for farm labour. Micevska and Rahut (2008) concluded that household assets, household characteristics, and location characteristics played important roles in explaining participation in nonfarm activities..…”
Section: Number Of Secondary Income Generating Activities and Demogramentioning
confidence: 99%
“…According to IFAD (2001), poverty remains predominantly a rural phenomenon despite rapid urbanization observed in most developing and transition countries. There are over one billion youth (aged [15][16][17][18][19][20][21][22][23][24] in the world, 85 percent of these youth live in the developing countries and about 50 percent of youth population in developing countries live in rural areas (United Nations, 2007). They constitute a reasonable force propelling rural economy, nonetheless, poverty is still pervasive among rural youth who face numerous challenges in order to achieve and maintain their livelihoods.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, rural households are forced to look at alternative non-agricultural income generating activities for their survival. Micevska and Rahut (2008), reported that the rural poor engage in non-farm activities, both as a compliment to their farm activities and as a substitute for their farm incomes. Concomitantly, there has been increasing involvement of youth in rural non-farm income generating activities like craft work, trade and employment in both unorganized and organized nonagricultural private sectors (Reardon et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, income dynamics could be influenced by more longer-term trends away from agriculture. Particularly, engagement in high-productivity, non-agricultural activities can be most conducive towards income growth and poverty reduction, especially in the presence of poor physical infrastructure and human capital constraints (Ravallion and Datt, 1996, 1998b, 2002Lanjouw and Lanjouw, 2001;Elbers and Lanjouw, 2001;Micevska and Rahut, 2008). This article's principal objective is to examine the sources of income growth in rural Indonesia since the late 1990s.…”
Section: Introductionmentioning
confidence: 99%